Oncologists' Communication About Uncertain Information in Second Opinion Consultations: A Focused Qualitative Analysis - van Someren, Jamie L.; Lehmann, Vicky; Stouthard, Jacqueline M.; Stiggelbout, Anne M.; Smets, Ellen M. A.; Hillen, Marij A. (Frontiers in Psychology, 2021)
Introduction: Uncertainty is omnipresent in cancer care, including the ambiguity of diagnostic tests, efficacy and side effects of treatments, and/or patients’ long-term prognosis. During second opinion consultations, uncertainty may be particularly present: doubts and uncertainty may drive patients to seek more information and request a second opinion, whereas the second opinion in turn may also affect patients’ level of uncertainty. Providers are tasked to clearly discuss all of these uncertainties with patients who may feel overwhelmed by it. The aim of this study was to explore how oncologists communicate about uncertainty during second opinion consultations in medical oncology. Methods: We performed a secondary qualitative analysis of audio-recorded consultations collected in a prospective study among cancer patients (N=69) who sought a second opinion in medical oncology. We purposively selected 12 audio-recorded second opinion consultations. Any communication about uncertainty by the oncologist was double coded by two researchers and an inductive approach was chosen to allow for novel insights to arise. Results: Seven approaches in which oncologists conveyed or addressed uncertainty were identified: (1) specifying the degree of uncertainty, (2) explaining reasons of uncertainty, (3) providing personalized estimates of uncertainty to patients, (4) downplaying or magnifying uncertainty, (5) reducing or counterbalancing uncertainty, and (6) providing support to facilitate patients in coping with uncertainty. Moreover, oncologists varied in their (7) choice of words/language to convey uncertainty (e.g., “I” vs. “we”; level of explicitness). Discussion: This study identified various approaches of how oncologists communicated uncertain issues during second opinion consultations. These different approaches could affect patients’ perception of uncertainty, emotions provoked by it, and possibly even patients’ behavior (e.g., by minimizing uncertainty, oncologists may (un)consciously steer patients towards specific medical decisions). Future research is needed to examine how these different ways of communicating about uncertainty affect patients. This could also facilitate a discussion about the desirability of certain communication strategies. Eventually, practical and evidence-based guidance needs to be developed for clinicians to optimally inform patients about uncertain issues and support patients in dealing with these.